Upaya promotif peningkatan pengetahuan tentang imunisasi lanjutan measles rubella dengan aplikasi ponsel AIMMER - Nur Djanah; Yuliantisari Retnaningsih (Poltekkes Kemenkes Yogyakarta, 2021)
Advanced immunization of Measles Rubella (MR) is an effective strategy to achieve high immunization coverage that will form herd immunity and break the chain of transmission of Measles and Rubella disease. Utilization of the development of android smartphone technology is very possible to develop a system that replaces the role of an expert in the field of health. The purpose is to increase the knowledge of cadres and mothers about the concept of advanced immunization MR through the Android-based application